PENGARUH ORIENTASI ETIKA, KOMITMEN PROFESI, DAN KOMITMEN ORGANISASI TERHADAP SENSITIVITAS ETIKA (Studi Empiris Pada Kantor Akuntan Publik di Semarang). - Hartono, Stephanus (Jurnal Akuntansi Bisnis, 2012)
This study aims to provide empirical evidence of the influence of the ethical orientation of idealism and relativism, professional commitment and organizational commitment have an influence on auditors ethical sensitivity. The research was conducted in the city of Semarang, Central Java province with the study sample auditors who worked at public accounting firms in Semarang and the sampling technique used was purposive sampling. Data collected in this study with 45 copies of the questionnaire that was sent to nine public accounting firms in the city of Semarang, however, 45 copies of the questionnaire only 38 copies of the questionnaire is suitable as sources of research data. Methods of data analysis used were multiple analysis methods to examine the direct effect between the independent variables on the dependent variable. The results provide evidence that the idealism and commitment to professional ethics orientation has a positive influence on the sensitivity of ethics, whereas ethical relativism orientation has a negative effect on ethical sensitivity. But the professions commitment does not have an influence on ethical sensitivity.